The identity of Actinodaphne sessilifructa (Lauraceae) - Zhou, Jian-Jun; Wu, Lei; Wu, Shao-Wu (Phytotaxa, 2018)
Examination of specimens and relevant literature and field investigation reveal that Actinodaphne sessilifructa is a representative of Litsea rather than Actinodaphne. A new combination, Litsea sessilifructa, is proposed.